The Effect of Potassium and Sulfur Fertilization on Seed Quality of Faba Bean (Vicia faba L.) - Przemysław Barłóg; Witold Grzebisz; Remigiusz Łukowiak (Agronomy, 2019)
Faba bean seeds are regarded as a highly valuable protein source for human and animal nutrition. High yield and quality of faba bean require adequate mineral nutrition. The aim of the study was to assess the impact of potassium (K) and elemental sulfur (S) on crude protein (CP) and tannin content (TC) in seeds, crude protein yield (CPY), and amino acid (AA) composition. Field trials were carried out during 2010−2013 in the temperate climate of Central Europe. The study assessed the influence of the following factors: variable soil K content and fertilization (K1, K2, K3, and K4) and elemental S application (0, 25, and 50 kg S ha−1). Plants were harvested at two growth stages to obtain immature seeds and mature seeds. K and S applications did not have a significant impact on CP and AA composition, including sulfur AA content. The TC decreased in response to increasing content of plant-available K in soil. In respect to CPY, the results indicate a positive response of faba bean to increasing K content in soil. The effect of S fertilization depended on the K treatment. The most beneficial influence of S on CPY was registered on K-poor soil.